DISCOURSIVE MEANS OF IMPLICATION OF INSTRUCTIVE COMPONENTS WITHIN THE ANTI-UTOPIA GENRE - Olga Vitalievna Khorokhordina (Филологический класс, 2016)
The author of the article characterises the instructive type of text and the anti-utopia genre based on criteria of definition of the genre of speech, formulated by M. M. Bakhtin. The article notes that the content of an anti-utopia reflects a negative image of the future society, based on a negative perception of the current social reality. The aesthetic intention of a writer, creating an anti-utopia, is to stimulate the reader to consciously define his/her civic attitude towards the existing state of affairs in the society. The author of the article shows that normally the anti-utopia genre must imply an instructive component, containing the answer to the question: «Which tendencies of contemporary life are to be eradicated in order to avoid the social situation described in the antiutopia?» The article analyses the anti-utopic short story «Marfusha’s joy» by V. Sorokin and shows that the writer uses not only the content but also an artificially constructed language of the future as a mean to form the image of negative social tendencies. Taking into account the nature of this language the author of the article names it «futurespeak». The author of the article notes that futurespeak is dominated by 7 main discourses, that mark the 7 negative (from Sorokin’s point of view) tendencies in the development of the contemporary society.